Vertical and horizontal pullout capacity of mooring lines embedded in very soft clays. (15th August 2021) - Sampa, Naloan Coutinho; Schnaid, Fernando; Rocha, Marcelo Maia; Cudmani, Roberto; Amaral, Claudio dos Santos
Abstract: Mooring lines are widely used to connect offshore platforms to anchors embedded in the seabed. The configuration of the inverse catenary formed by mooring lines influences the installation of the anchors, the load capacity and the anchors failure mode. For this reason, a proper understanding of the soil-chain interaction is a requirement for an accurate prediction of the configuration of the inverse catenary. This paper presents the main results of a laboratory investigation program carried out on a scale-reduced model to study the interaction mechanism between clay and the steel chain of different diameters, lengths and stiffness. Some aspects related to the inverse catenary and tension distribution, such as the shaft and base resistances, adhesion and bearing capacity factors, effective width in sliding, strain-softening, and displacement at the maximum load were extensively discussed herein. Comparisons between these results and the background experimental data used to support general engineering practice have been made for the different aspects investigated. The chain geometry, stiffness, direction of chain displacement and soil properties influence the behavior of the measured curves and, consequently, the corresponding soil-chain interaction. From a practical point of view, the results presented are beneficial for understanding the chain-soil interaction and show an explicit potential to contribute to the optimization of the offshore foundation engineering involving inverse catenary design problems. Highlights: Inverse catenary mainly depends on the mooring line geometry and soil properties. The soil-soil interaction controls the pullout capacity of the mooring lines in clays. Chain stiffness governs the magnitude of the displacement to mobilize the maximum pullout capacity.